Astrocytic Contribution to Glutamate-Related Central Respiratory Chemoreception in Vertebrates - Eugenin-Leon, J; Olivares-Arce, M (Elsevier B.V., 2021)
Central respiratory chemoreceptors play a key role in the respiratory homeostasis by sensing CO2 and H+ in brain and activating the respiratory neural network. This ability of specific brain regions to respond to acidosis and hypercapnia is based on neuronal and glial mechanisms. Several decades ago, glutamatergic transmission was proposed to be involved as a main mechanism in central chemoreception. However, a complete identification of mechanism has been elusive. At the rostral medulla, chemosensitive neurons of the retrotrapezoid nucleus (RTN) are glutamatergic and they are stimulated by ATP released by RTN astrocytes in response to hypercapnia. In addition, recent findings show that caudal medullary astrocytes in brainstem can also contribute as CO2 and H+ sensors that release D-serine and glutamate, both gliotransmitters able to activate the respiratory neural network. In this review, we describe the mammalian astrocytic glutamatergic contribution to the central respiratory chemoreception trying to trace in vertebrates the emergence of several components involved in this process. © 2021 Elsevier B.V.
Keywords: Ionotropic glutamate receptors; Glutamate; Glycine site; D-serine; NMDA receptor; Evolution